HUBUNGAN EQ (Emotional Quotient) DENGAN HASIL BELAJAR MAHASISWA BIOLOGI SEMESTER GANJIL TAHUN AJARAN 2014/2015 - Ali Sadikin (BIODIK, 2015)
ABSTRACT   Emotional intelligence (Emotional Quotient) is an extra skill of an individual to motivate him or herself, to survive from a failure, to control the emotion, to hold over the comfort state of life, and to manage his or her soul. So, one of the important factors that influence the students’ success in learning is the emotional intelligence. This descriptive-quantitative study was aimed to determine the relationship between emotional intelligence and the students’ learning outcomes at the Basic and Process of Biology Students 2 Course of odd semester in the academic year 2014/2015. The population of the study was the third semester students. The emotional intelligence data were collected through a questionnaire in the form of statements. Data analysis techniques to determine the relationship between emotional intelligence and learning outcomes were conducted through statistical testing using simple linear regression. The results showed that the average emotional intelligence of the students obtained was 2.84 with a scale range between 2.00 to 2.99 which means that the value is low, and the emotional intelligence data frequency distribution of the students were 18.4% higher, 66.23% moderate, and 15.37% lower. Moreover, the scores of the emotional intelligence questionnaire and the students’ learning outcomes formed a linear model Y=61. 03+0.133X. Further, the correlation analysis between the emotional intelligence and the learning outcomes showed that r count have a correlation between variables X and Y with the value of r count =0.177 and the scores of t count > t table or 2.318 > 1.96 at 95% of the confidence level were indicating a significant correlation between emotional intelligence and learning outcomes.   Keyword: Emotional Intelligence and learning outcomes